Assessing environmental and economic dynamics in the EU agri-food sector: The impact of imports through a BVAR analysis - Eleni Zafeiriou; Spyridon Galatsidas; Georgios Tsantopoulos; Spyridon Sofios; Siakou Evangelia; Garyfallos Arabatzis (New Medit)
The study investigates the environmental impact of the EU agri-food sector, focusing on emissions per capita and their relationship with economic growth through a Bayesian Vector Autoregression (BVAR) framework. It reveals that greening efforts in the sector have not been matched by sufficient economic growth, challenging the Environmental Kuznets Curve (EKC) hypothesis. Despite progress in sustainable practices, economic expansion has fallen short of offsetting environmental costs, with imports playing a critical role. The Carbon Border Adjustment Mechanism (CBAM) under the EU Green Deal highlights the need to address trade-related emissions. The study calls for future research to develop a comprehensive index incorporating diverse variables to better assess sustainability efforts in the agri-food sector.